MAKNA TANGGUNG JAWAB SOSIAL DALAM STUDI KREATIF GENRE IKLAN DI TELEVlSI - Handriyotopo, Handriyotopo (Acintya, 2009)
The development of television media is quickly enough. in indonesia, many television advertisements appear to support the media. Advertisement which is formerly only comercial and non comercial (ILM) advertisement, nowadays there comes a kind of corporate advertisement but it has social nuance because of CSR (Corporat Social Responsibility) or philanthropy support so that the advertisement becomes a new advertisement called philanthropy advertisement. As the factory responsibility towards society, philanthmpy advertisement is usually presented appropriately with the suitable moment in order that the presented advertisement is exactly on target. To understand the meaning of philanthropy advertisement can be reached by catching the audiovisual advertisement by taking picture frame by frame from moving image advertisement The first thing to do is deconstructing the signs including icons, index, and symbols. The second step is interpretating denotative as well as conotative meaning of the myth from cultural values by narrative, descriptive, and inductive description. By post structuralist semiotics, television advertisement in one moment can be analized in relation to the form and content of message, moment or cultural context, artistic visual aspect offrame by frame as well as the movement in creating advertisement from its sign and signer. A sign is a game so that the signer is free from meaning. in other words, meaning presents because of intertextual sign and a text can be given a meaning freely and endlessly.Key words: meaning, philantrophy, culture